What the Bible says about abortion, euthanasia, and end-of-life medical decisions - Grudem, Wayne A. (Wheaton, Illinois : Crossway, 2020)
"Abortion and euthanasia are among the most controversial topics in society today. Abortion is simply any action that intentionally causes the death and removal from the womb of an unborn child. Likewise, Euthanasia is the act of intentionally ending the life of a person who is elderly, terminally ill, or suffering from some incurable injury or disease. In this book, Dr. Wayne Grudem attempts to give an accurate summary of biblical teachings related to abortion and euthanasia, and also to represent fairly the arguments of people who disagree with his positions"--
Includes bibliographical references and indexes
Keywords: Christian ethics -- Biblical teaching; Abortion -- Religious aspects -- Christianity; Abortion -- Biblical teaching; Euthanasia -- Religious aspects -- Christianity; Euthanasia -- Biblical teaching